Potential agency problems in European club football? The case of UEFA Financial Fair Play. Issue 4 (7th October 2014) - Harald Dolles; Professor Sten Söderman, Professor; Schubert, Mathias
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – With the licence season 2013/2014 onwards Union of European Football Associations (UEFA) Financial Fair Play (FFP) fully came into force. Among other things, FFP demands from the clubs to operate within their own revenues in order to counteract the increasing over indebtedness in European club football. The purpose of this paper is to cast further light on the relationship between UEFA and the clubs as the main actors of FFP and to derive implications to UEFA to improve the efficacy of this regulatory intervention. Design/methodology/approach – This paper explicitly examines the case of FFP from an agency theory perspective. A positivist agency approach is applied in order to describe and explain (potential) problems in the relationship between UEFA and the clubs. Findings – The paper demonstrates that the relationship between UEFA and the clubs corresponds in many aspects to a classic principal-agent problem. A potential conflict of interest between both actors is outlined which together with asymmetric information creates incentives for opportunistic behaviour on the part of the clubs. The necessity of a stronger emphasis and communication of the economic and sport ethical legitimacy of FFP is detected. Practical implications – It is suggested that UEFA should consider taking a more proactive stance and endeavour to prevent non-compliance not only by limiting the opportunities to do so but also by providing information as well as education. Originality/value – FFP is supposed to have ground-breaking consequences for European club football. This is the first paper to systematically examine (potential) agency problems inherent in FFP.